Hak Privasi dan Hak Citra dalam Penggunaan Foto Berbasis Artificial Intelligence (AI) - Alfin Dwi Novemyanto (CV. Era Digital Nusantara, 2025)
The development of Artificial Intelligence (AI) has transformed photographs from factual records into digitally manipulable representations that can be widely disseminated, giving rise to new legal issues concerning the use of images without consent. This phenomenon underscores the urgency of strengthening the protection of privacy rights and image rights, as AI-based photo usage may infringe human dignity, personal autonomy, and the right to self-determination. This study aims to analyze the legal construction of AI-based photo usage without consent and its implications for the protection of privacy and image rights within the framework of national law and human rights principles. The research employs a normative juridical method, using statutory, conceptual, and limited comparative approaches. The findings indicate that the existing regulatory framework remains fragmented and does not specifically govern AI-based image manipulation, resulting in legal uncertainty. Accordingly, this study argues for a strengthened legal framework that places consent as a central principle in the lawful use of digital images in the AI era.